A current affair: entanglement of humpback whales in coastal shark‐control nets. Issue 2 (21st November 2019) - Bolin, Jessica A.; Schoeman, David S.; Pizà‐Roca, Carme; Scales, Kylie L.
Abstract: Shark‐control nets pose an entanglement risk to East Australian humpback whales during their annual northward and southward migrations between the Southern Ocean and the Coral Sea. Rates of whale entanglement exhibit seasonal and interannual variation, suggesting that an understanding of the influence of variability in the broad‐scale physical environment along the migratory route would be useful in assessing risk of entanglement. This study provides a quantitative spatio‐temporal analysis of the probability of whale entanglement in shark‐control nets relative to the position and characteristics of the East Australian Current (EAC), the dominant oceanographic feature of the region. We use satellite‐derived sea‐surface temperature, and outputs from a data‐assimilating ocean model, to develop multivariate, data‐driven algorithms for detecting the edge of the EAC using Principal Components Analysis. We use outputs from these algorithms to model the likelihood of humpback entanglements in South‐east Queensland. We find that the likelihood of entanglement increases when the EAC edge is locally less structured and closer to shore in the vicinity of the corresponding net, or when the EAC is well resolved over the entire study domain. Our results suggest that migrating humpbacks use the gradient in physical characteristics that marks the EAC inner edge as a navigational aid. Thus, when the EAC inner edge encroaches on the coast, the whales' migration range is compressed into nearshore waters, increasing the risk of entanglement. Our findings can help predict periods of elevated entanglement risk, which could underpin a more data‐driven approach to the management of shark‐control programs, and other activities that involve static fishing gear. Abstract : This study provides a quantitative spatio‐temporal analysis of the probability of whale entanglement in Southeast Queensland shark‐control nets, relative to the position and characteristics of the East Australian Current (EAC). We find that the likelihood of entanglement increases when the EAC edge is locally less structured and closer to shore in the vicinity of the corresponding net, or when the EAC is well‐resolved over the entire study domain. Our results suggest that migrating humpbacks use the gradient in physical characteristics that marks the EAC inner edge as a navigational aid. Thus, when the EAC inner edge encroaches on the coast, the whales' migration range is compressed into nearshore waters, increasing the risk of entanglement.